Development of Teaching Materials on National Historiography - Indah Lestari, Nur; Saputra, Chery; Suparjan, Edy (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Teaching materials are comprehensive learning resources compiled in accordance with the established syllabus and aligned with learning principles and students’ learning needs. The objective of this study focuses on the development of teaching materials for National Historiography that are suited to students’ learning styles and the challenges of higher education. The research method employed is Research and Development, utilising the ADDIE model, which comprises several stages: analysis, design, development, and implementation. The results of the material validation test, using 20 indicators, yielded a score of 87% out of 100%, with a recommendation of ‘highly suitable’. The instrument used in the expert review was an expert validation sheet designed as a Likert-scale questionnaire to assess the suitability of the product from a content perspective. The product’s effectiveness was tested using a questionnaire administered to a limited group. Based on the questionnaire results, it was found that the presentation of the material in the National Historiography textbook was rated as ‘very good’ by 36.4% of respondents, whilst 60.6% rated it as ‘good’. The presentation of the National Historiography textbook was rated as good and appropriate for students’ learning needs because the material was structured, the layout was neat, and the use of tables and summaries helped to clarify the content and made the book visually appealing and practical to use.